The influence of Cu, Mn micronutrients on some biochemical indicators and the post-haverst preservation duration for tomatoes (Lycopersicon esculentum L.) - Thu, Vo Minh; Hue, Truong Thi (Academia Journal of Biology, 2012)
Tomatoes contain many beneficial nutrients to the body as carotene, vitamins and mineral elements. There are many ways to increase in productivity and quality of these cultivars, including the fertilizer of micronutrients. CuSO4 0.02%, MnSO4 0.03% solution and their mixture were treated to F1 France tomato in the stages before bud formation, in bud and in 25% ripening. Control variant was treated to which by distilled water. We conducted flow-up time preserving tomatoes at room temperature (22-25oC), at refrigerator temperature (8oC) with polyethylene bags and without polyethylene bags. Some biochemical indices of tomato fruits during ripening was analysed Our results showed that the treating of Cu, Mn micronutrients have active effects to some biochemical indices and preservation duration of tomatoes. Chlorophyll content increased the most in CuSO4 0.02% variant (0.360 mg/g), followed MnSO4 0.03% (0.247 mg/g) and the lowest is the mixed variant (0.25 mg/g) compared with control (0.247 mg/g). Carotenoid content in fruits of tomato in the experimental variants are higher than that compared with control, in particular, organic acid content of fruits through the ripening periods in CuSO4 0.02% variant increased up 14.59% in 25% ripening fruits and 11.08% in 50% ripening fruits. Reduced sugar content in ripening fruits at various stages in the experimental variants war increased to compare with control. In particular, in CuSO4 0.02% variant accumulated reduced sugar content in fruits reached the highest value (2.95 mg/100g) increased 3.15% compared with control (2.86 mg/100 g) in the period of 25% ripening fruits. Treating micronutrients, organic acid content increased compared with control at all stages of maturity. However, the mixed treatment is most effective (up 23.21%). Treating micronutrients resulted in formation levels of vitamin C were higher compared with control in the third stage of ripening fruits, in which the variant is mixed treatment reached the highest value, up 13.29% in 25% ripe fruits, 17.48% in 50% ripe fruits and 25.54% in 100% ripening fruits. Cu and Mn content too little change over the periods of fruit ripening, with Cu and Mn content in the fruits that we have analysed, do not exceed standard level on food safety. The treated variants by CuSO4 0.02% and MnSO4 0.03% were increased in storage time for tomatoes at room temperature 22-25oC from 0.6 to 3.0 days and at 8oC from 0.3 to 6.1 days, especially, MnSO4 0.03% is most effective.